RANCANG BANGUN SISTEM PEMANTAUAN GETARAN KERETA REL LISTRIK COMMUTER LINE SECARA ONLINE - Erna Kusuma Wati; Fraska Anangga (FTK UNSURYA, 2020)
Dense settlements around the railroad track need a vibration monitoring device that can monitor the acceleration of vibrations. The level of risk of exposure to waves can cause health problems. A vibration measuring device can determine the acceleration value of a passing KRL vibration so that it can be as a reference in establishing settlements. This research has succeeded in designing a KRL vibration measurement system and can display it online, using the ADXL345 accelerometer sensor, Arduino Uno board, and ESP8266 Module. The sensor will detect changes in vibration around the railroad tracks when passed by a passing train. Furthermore, the data is sent to the webserver using the ESP8266 Module. The impact of vibrations generated by the moving train can cause health problems in the long run with a distance of ± 5 meters from the railroad tracks. The wave to show with the most substantial value at a distance of 1 meter from the railroad was 0.983507 m / s², at a distance of 5 meters from the railroad was 0.491333 m / s², At a distance of 9 meters from the railroad was 0, 12 m / s², and at a distance of 13 meters from the railroad tracks of 0.026 m/s.